Long-term mechanical stability of cemented incineration bottom ash. (15th September 2015) - Weng, Meng-Chia; Wu, Min-Hao; Lin, Chiou-Liang; Syue, Da-Ken; Hung, Ching
Graphical abstract: The strength clearly decreased as the Al2 O3 proportion increased and this trend existed in the short-term (14 days) and long-term (365 days). Therefore, regardless of whether the bottom ash was cemented or not, the increase in Al2 O3 content was disadvantageous to its mechanical properties, including friction angle, compressive strength, tensile strength, and deformation modulus. Therefore, the Al2 O3 content should be strictly controlled during bottom ash recycling to ensure that the incineration bottom ash has better engineering properties. Highlights: As Al2 O3 increases, uniaxial compressive strength and tensile strength will decrease. The strength of the specimen in the acid solution is lower than alkaline solution. As the age increases, the strength of specimen will increase, but the strength converts to decrease after 180 days. Long term stability of bottom ash with high Al2 O3 is not suitable for application. Abstract: Al2 O3 is a major constituent of municipal solid waste (MSW) bottom ash that may cause swelling and weakening failure. This paper explores the influence of Al2 O3 on the long-term mechanical properties of bottom ash. Experimental results indicate that increased Al2 O3 corresponds to decreases in both the uniaxial compressive and tensile strengths of cemented bottom ash. More specifically, the strength and Young's modulus of cemented bottom ash with high Al2 O3 content (9.2%) decreased by 22.1% and 40.1%, respectively, after 365 days. Therefore, the long-term mechanical stability of bottom ash with a high Al2 O3 content is unsuitable for engineering applications.